Young Adult, Adult Learner and Faculty Perceptions on the Integration of Diversity and Social Justice Education in the Classroom - Reba Fuggs; Robert F. Reardon; Amanda R Young (Adult Education Research Conference, 2019)
As diversity within the classroom soars, evaluating the curriculum and assessing perceptions about the integration of diversity and social justice education is integral.
Keywords: diversity; social justice; classroom; faculty perceptions; adult learner perceptions